Step-by-step explanation:
For the system of equations given below
![\begin{gathered} y=-(1)/(2)x \\ x^2+y^2=20 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/sod9xhw0yzfh3l2hxwra8u4ascg6mqti65.png)
If we are to solve, we will simply substitute y=-1/2x into the second equation, so that
![\begin{gathered} x^2+(-(1)/(2)x)^2=20 \\ x^2+(1)/(4)x^2=20 \\ (4x^2+1x^2)/(4)=(5)/(4)x^2=20 \\ \text{cross multiply} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/mnk3hc2z5247dtombhajz0dhxwgrlgja41.png)
![\begin{gathered} x^2=(20*4)/(5) \\ x^2=16 \\ x=-4 \\ \text{and} \\ x=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/erelle4wlce7b9qlp3lmny251f2o0nuxsc.png)
The next step will be to substitute x=4 and x=-4 into the equation to get the required values of y
When x=4
![\begin{gathered} y=-(1)/(2)x \\ y=-(1)/(2)(4)=-2 \\ \text{Thus one of the pair is} \\ (4,-2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/3pjnphzxlr6bd9rndeaz31aqei8dyfeyhn.png)
Also,
When x=-4
![\begin{gathered} y=-(1)/(2)x \\ y=-(1)/(2)(-4) \\ y=2 \\ \text{Thus, the second pair is} \\ (-4,2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/s7l4ekjh31heytdwwsml4i6xq6d362bg0i.png)
Hence, the answers are: Options B and D